PENGARUH PERMAINAN CARRYING BALL ON POLES TERHADAP PERKEMBANGAN SOSIAL ANAK DI TAMAN KANAK-KANAK DELIMA BANDARA - Damayanti, Melly; Serli Marlina (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This research is motivated by the suboptimal social development of children in the current technological era, where excessive device usage has hindered the growth of their cooperation, communication, and independent conflict-resolution skills. The primary objective of this study is to examine the effect of the collaborative game